2020
DOI: 10.2340/16501977-2672
|View full text |Cite
|
Sign up to set email alerts
|

A "Neuromuscular Look" to sarcopenia: Is it a movement disorder?

Abstract: Decline of physical function is the main cause of morbidity and mortality in sarcopenia and frailty. Physical function tests are performed to show the daily functional tasks. The central nervous system initiates, coordinates and controls muscle movements. Thus, the ability of a muscle to produce force by aging is determined not only by skeletal muscle, but also by neuromotor control systems. Therefore, treatments should contain targeting muscle mass and also neurocognitive functions. In this regard, an example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…Evidence showed that the primary motor cortex (M1) contributes to the control of a power grip of finger muscles during a variety of grasping behaviors 55 . Kara et al demonstrated that neuromotor control dysfunction contributes to the deterioration of the force generating capacity of skeletal muscles 56 . More research is needed to verify this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence showed that the primary motor cortex (M1) contributes to the control of a power grip of finger muscles during a variety of grasping behaviors 55 . Kara et al demonstrated that neuromotor control dysfunction contributes to the deterioration of the force generating capacity of skeletal muscles 56 . More research is needed to verify this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, the neuromuscular system, including the central nervous system, is responsible for the generation of force for muscle functions—that is, handgrip strength and gait speed (the “vital signs” for assessment of the neuromusculoskeletal system). Therefore, these parameters are likely to be related to cognition, as well as muscle mass 4 . Likewise, the authors found low Mini Mental State Examination scores in the sarcopenic group (with low grip strength).…”
mentioning
confidence: 84%
“…It is desirable that future proposals for health measures will focus on solutions to strengthen the physical capacity of the population, including neurocognitive stimulation (Kara et al, 2020), which can provide an example of long-term physiotherapy support and intergenerational integration through rehabilitation offer to maintain physical fitness and active lifestyle.…”
Section: Ageing Controlmentioning
confidence: 99%